THE STATE OF CONDITIONS AND CHALLENGES FACED BY INTERNALLY DISPLACED WOMEN (IDW) IN NIGERIA: A SOCIAL INCLUSION PERSPECTIVE (Journal of International Studies, 2021)
This paper examined the state of conditions and challenges encountered by internally displaced women (IDW) at three selected internally displaced persons (IDPs) camps in Malkohi, Fufore and Durumi. This study was conducted in an attempt to create awareness of the conditions of IDW at IDPs camps in Nigeria. It captured theexperiences and livelihoods of IDW at the camps and generated information on the state of conditions and challenges of the IDW through human security concept, empowerment and social inclusion theory. The study employed a narrative interview for data collection and thematic analysis for data analysis. It revealed that IDWencountered various forms of challenges ranging from economic challenges to absence of social networks and lack of targeted support. The responses of the IDW revealed inadequate measures by the government to enhance their standard of living at the camps. It is important to note that ensuring the protection and safety of IDW should extend beyond providing shelter and adequate facilities, to include provisions to protect their rights, ensure adequate livelihood and equal economic opportunities.